Busana Tari Bedhaya Ragam Hias Dan Makna Simboliknya = Costume of Bedhaya Ketawang Dance: Array of Decorations and Symbolical Meaning - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT This study intends to describe the arrays of ornaments, their representations and functions of the 'Bedhaya Ketawang' dance, the royal female dance of Kasunanan Surakarta (Surakarta Kingdom). This ritual and mystical dance is only performed in the king coronation ceremony and he anniversaries. Rehearsal for this sacred dance could only happen on Anggara Kasih day (Tuesday Kliwon), that is a combination of the seven week days and the Javanese 5 days which, therefore, repeats after 35 days. The story of this cultural dance dated long back to the moment when Panembahan Senapati converged the Queen of the South Sea (the Indian Ocean), or also named The Queen Kencanasari. Data collection for this descriptive study based library research, observation and interviews. The findings suggest that the array of decorations on the costume, the face making and the jewelries, each symbolize all messages comprise in the dance. In other words, the details of decorations have been all needed elements which represent the ritual and ceremonial message, that support the legitimacy of and to the king to rule the kingdoms, the Kasunanan.